Adipose Tissue-Derived Stem Cells Alleviate Cold Allodynia in a Rat Spinal Nerve Ligation Model of Neuropathic Pain. (12th October 2020) - Jwa, Hyeon Seok; Kim, Yong Ho; Lee, Jaehee; Back, Seung-Keun; Park, Chul-Kyu
Abstract : Neuropathic pain caused by lesions or nervous system dysfunction is a neuroimmune disease with limited therapeutic options. Adipose tissue-derived stem cells (ASCs) are multipotent mesenchymal stem cells with potent immunosuppressive properties, and their use as novel cell-based therapeutics have been proposed in many immune diseases. However, the analgesic effect and efficacy of ASCs to treat neuropathic pain remain unclear. This study, thus, investigated whether ASCs or ASC-derived culture medium can relieve neuropathic pain behaviors (i.e., mechanical and cold allodynia) in a rat model with L5 spinal nerve ligation. Intrathecal injection of ASCs significantly reduced cold allodynia, but not mechanical allodynia. Importantly, cold allodynia was completely reversed in rats with repeated injections of ASCs. In contrast, intrathecal injection of ASC-derived culture medium or retro -orbital injection of ASCs had no effect on neuropathic pain behaviors. These results suggest a novel and alternative therapeutic application of ASCs to target specific neuropathic pain behaviors.